IS IT POSSIBLE TO HAVE IN RUSSIA OUR OWN STANFORD? - Vladimir A. Zernov (Moscow Polytechnic University, 2016)
The article covers a number of questions concerning the role and the place of non-governmental universities in Russian education system. The authors stresses that the public and national universities have a privileged status, and the position of a non-governmental sector depends on the presence of a competitive environment. Realization of measures aimed at attainment of the equality of different types of universities can bring our education system to conformity with the world trends in this sphere.